Un Dio per l'uomo: La teologia alternativa di Armido Rizzi - Fabrizi, Fabrizio (Rassegna di teologia, 2021)
Armido Rizzi elaborates an alternative approach to the classical theology on Christian revelation. His is an original attempt at the dehellenization of Christian theology. Rizzi's theological method encounters the true meaning of revelation not so much in traditional metaphysical models and language as much as in the religious language of the Bible. He does not give up thinking God, however he thinks God not beside but inside the Bible. (English)